Financial and Monetary Cooperation in ASEAN - Mario B. Lamberte; Josef T. Yap (Philippine Institute for Development Studies (PIDS), 2003)
One result of the 1997 East Asian financial crisis was greater awareness of the need for closer financial and monetary cooperation. This paper makes an inventory of the institutional developments in this area in East Asia, with emphasis on Southeast Asia. The major issues that must resolve include: (i) whether the participation should be limited to ASEAN or expanded to include the whole East Asia region; (ii) the sequencing of activities; and (iii)the institutions that must be consolidated or established to carry out these activities. Since financial and monetary integration remain a distant goal, efforts must focus on monetary and financial cooperationparticularly the latter, mainly in terms of harmonization of standardsthat will facilitate greater trade and investment integration and enhance financial stability in the region.
Keywords: 330; regional integration; monetary and financial cooperation; Internationale Wirtschaftspolitik; Regionale Wirtschaftsintegration; Finanzpolitik; Geldpolitik; ASEAN-Staaten